Comparison of methods based on different molecular epidemiological markers for typing of mycobacterium tuberculosis complex strains: interlaboratory study of discriminatory power and reproducibility - Kremer, Kristin; Soolingen, D. van; Frothingham, R.; Haas, Walter; Hermans, P. W. M.; Martín, C.; Palittapongarnpim, P.; Plikaytis, B. B.; Riley, L. W.; Yakrus, M. A.; Musser, J. M.; Embden, J. D. A. van (Journal of clinical microbiology, 1999)
ABSTRACT In this study, the currently known typing methods forMycobacterium tuberculosis isolates were evaluated with regard to reproducibility, discrimination, and specificity. Therefore, 90 M. tuberculosis complex strains, originating from 38 countries, were tested in five restriction fragment length polymorphism (RFLP) typing methods and in seven PCR-based assays. In all methods, one or more repetitive DNA elements were targeted. The strain typing and the DNA fingerprint analysis were performed in the laboratory most experienced in the respective method. To examine intralaboratory reproducibility, blinded duplicate samples were included. The specificities of the various methods were tested by inclusion of 10 non-M. tuberculosis complex strains. All five RFLP typing methods were highly reproducible. The reliability of the PCR-based methods was highest for the mixed-linker PCR, followed by variable numbers of tandem repeat (VNTR) typing and spoligotyping. In contrast, the double repetitive element PCR (DRE-PCR), IS6110 inverse PCR, IS6110 ampliprinting, and arbitrarily primed PCR (APPCR) typing were found to be poorly reproducible. The 90 strains were best discriminated by IS6110 RFLP typing, yielding 84 different banding patterns, followed by mixed-linker PCR (81 patterns), APPCR (71 patterns), RFLP using the polymorphic GC-rich sequence as a probe (70 patterns), DRE-PCR (63 patterns), spoligotyping (61 patterns), and VNTR typing (56 patterns). We conclude that for epidemiological investigations, strain differentiation by IS6110 RFLP or mixed-linker PCR are the methods of choice. A strong association was found between the results of different genetic markers, indicating a clonal population structure of M. tuberculosis strains. Several separate genotype families within the M. tuberculosis complex could be recognized on the basis of the genetic markers used.
Gesehen am 21.12.2020